Implementation of bioethics in nursing education - Leiva Díaz, Viriam (2014)
Background: the objective of this paper is to present the results after analyzing the description of the courses themselves belonging to the curriculum of the Degree Programme in Nursing from the University of Costa Rica.Method: was conducted through a literature review, documentary, archivist, he analyzed 27 courses specific to the Bachelor of Nursing. Of these courses extracted through an elaborate matrix that finally reflecting aspects implicitly or explicitly Human Rights and bioethics. Also analyzed in ethical approach reflected in the documents analyzed.Result: the practice of non-maleficence and beneficence in the values of Human Rights stands identified and others that reflect the principle of justice; this ethos is altruistic. From the theory of the ethics of care, the outlook I and II proposed by Gilligan stands apart from the social bioethics.Conclusion: fundamental values that are based on the principles of non-maleficence and beneficence describe the course sylabus. It is not clear how they will work in the teaching learning process